Throbbing headache associated with enoxaparin administration: a case report, a review of pharmacovigilance databases for similar cases and possible mechanisms. (2nd March 2015) - Brusadelli, T.; Carnovale, C.; Gentili, M.; Borsadoli, C.; Speziali, A.; Perrone, V.; Pellegrino, P.; Antoniazzi, S.; Pozzi, M.; Radice, S.; Clementi, E.
Summary: What is known and objectives: To date, no case of headache has been reported with enoxaparin. We present the case of a 60‐years‐old man, who developed enoxaparin‐induced throbbing headache and discuss the possible pharmacological mechanisms. We provide an analysis of enoxaparin‐induced headache in three international databases. Case summary: A few hours after the subcutaneous administration of this drug at therapeutic dose, the patient experienced throbbing headache. Rechallenge on two other separate occasions separated by several days produced the same effect although with reduced intensity when the dose was lowered. The Naranjo Algorithm indicated a 'certain' relationship. What is new and conclusion: We report a case of throbbing headache associated with the use of enoxaparin; with the increasing use of enoxaparin, physicians who prescribe this drug should be aware of this potential ADR. We suggest that it is a heparin class‐effect, and therefore, a more general caution is also appropriate. Abstract : Enoxaparin is generally safe but side‐effects related to pharmacological effect could occur, i.e haemorrhages and thrombocytopenia. We report a case of enoxaparin‐ induced throbbing headache, an unknown ADR, likely due to the stimulation of the release of nitric oxide (NO) and the increase of cyclic guanosine monophosphate (cGMP).